2021
DOI: 10.3390/min11060637
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Spent Reverse Osmosis Membranes for Second Use in the Clarification of Wet-Process Phosphoric Acid

Abstract: Various techniques have been used to “clean-up” wet-process phosphoric acid such as precipitation, flotation and adsorption. To address the potential of membrane processes in the phosphoric acid clarification process, this study explores the benefits of membrane techniques as a green separation technique for phosphoric acid clarification in an eco-efficient way through the use of recycling spent reverse osmosis membrane. Regenerated membrane was used to study the phosphoric acid clarification at a laboratory s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…So, the whole conversion with all the same details has been repeated one more time. The same concentration of NaOCl was applied a second time, and a net total of 2400 mL was used to convert the spent RO into an R-RO membrane [ 21 ]. The conversion procedure details are given in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the whole conversion with all the same details has been repeated one more time. The same concentration of NaOCl was applied a second time, and a net total of 2400 mL was used to convert the spent RO into an R-RO membrane [ 21 ]. The conversion procedure details are given in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Jawad in 2021 converted the RO membrane and tested it on the gray water that showed higher water recovery % and removal of E. coli [ 19 ]. Khaless et al in 2021 observed the salt rejection percentage of the RO spent membrane and proposed to use it for phosphoric acid treatment [ 20 , 21 ]. Salinas et al in 2020 evaluated the life cycle assessment (LCA) and direct economic analysis of recycling of RO membranes that showed positive results, and it proved effective as an environmental benefit, and recycled modules can be sold at a competitive price of 80 euros in the market [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This process was studied in detail during the study of aging of reverse osmosis membranes (Donose et al, 2013) or the impact on the web of various oxidants, namely chlorine compounds (hypochlorite, chlorine dioxide, chloramines, etc. ), hydrogen peroxide, ozone, potassium permanganate (Khaless et al, 2021;Kang et al, 2007;Moradia et al, 2019;Donose et al, 2013;Cran et al, 2011;Ling et al, 2019;Yu et al, 2019). As shown by several authors, in the latter case the polyamide layer changes its morphology, resulting in changes in its selectivity (Lawler et al, 2012;Goh et al, 2018;Paula et al, 2018;Pontie et al, 2017).…”
Section: Direct Recyclingmentioning
confidence: 99%
“…Subsequently, the transformed membrane could be utilized as an MF/UF element for pretreatment of the feed or for non-potable water reuse applications (Figure 3a). The primary approach involved in membrane downcycling is the partial or full destruction of the PA layer using oxidizing agents such as NaOCl [37], potassium permanganate (KMnO 4 ) [61], hydrogen peroxide (H 2 O 2 ) [62], and their mixture [63]. The utilization of NaOCl is perhaps more common for NF/RO membranes downcycling due to the susceptibility of PA to NaOCl, causing its degradation [22,[64][65][66].…”
Section: Polymeric Membrane Downcyclingmentioning
confidence: 99%